Hungarian Energy Prices in an OECD Comparison - Bartha, Zoltán (Theory, Methodology, Practice – Review of Business and Management, 2016)
The goal of the study is to assess the effect of the utility cost reductions announced by the Hungarian government in 2012 on Hungarian energy prices. The effects are discussed in an OECD comparison. It is concluded that the government price control has resulted in a 15% steeper price reduction occurring 5-7 quarters earlier, compared to other OECD countries. The price reductions saved around 202 billion HUF for Hungarian households in 2014, which was around 0.63% of the GDP. If prices are compared to the monthly average wages however, household energy prices are still high in Hungary. One of the costs of the reduction in household energy prices was an increase in energy prices for industry: the industry/household price ratio is highest among OECD countries in the case of natural gas, and third highest for electricity.